How the intracellular partitioning of tRNA and tRNA modification enzymes affects mitochondrial function - Paris, Zdeněk; Alfonzo, Juan D (IUBMB life, 2018)
Organisms have evolved different strategies to seclude certain molecules to specific locations of the cell. This is most pronounced in eukaryotes with their extensive intracellular membrane systems. Intracellular compartmentalization is particularly critical in genome containing organelles, which because of their bacterial evolutionary ancestry still maintain protein-synthesis machinery that resembles more their evolutionary origin than the extant eukaryotic cell they once joined as an endosymbiont. Despite this, it is clear that genome-containing organelles such as the mitochondria are not in isolation and many molecules make it across the mitochondrial membranes from the cytoplasm. In this realm the import of tRNAs and the enzymes that modify them prove most consequential. In this review, we discuss two recent examples of how modifications typically found in cytoplasmic tRNAs affect mitochondrial translation in organisms that forcibly import all their tRNAs from the cytoplasm. In our view, the combination of tRNA import and the compartmentalization of modification enzymes must have played a critical role in the evolution of the organelle. © 2018 IUBMB Life, 70(12):1207-1213, 2018.
Keywords: Mitochondria; mitochondria; intracelulární membrány; genom mitochondriální; RNA Processing, Post-Transcriptional; RNA, Transfer; Genome, Mitochondrial; mitochondrie; symbióza; posttranskripční úpravy RNA; wybutosine; import; RNA transferová; Symbiosis; Mitochondrial Membranes; Intracellular Membranes; trypanosomes; proteosyntéza; mitochondriální membrány; Cytoplasm; 1-methylguanosine; cytoplazma; Protein Biosynthesis